Implementation of Science and Technology in Indigofera and Sorghum Cultivation as Livestock Feed in Paluh Kurau Village - Banurea, Rahmadhani; Hilman, Adrian (Talenta Publisher, 2023)
The event was held in Paluh Kurau Village in May to October 2021. This activity partner is a cattle group in Paluh Kurau Village. The main problems faced by partners are the problem of livestock productivity that has not been optimal, preparation and feeding techniques that have not been effective and technology to feed sources of indigofera raw materials and sorghum that do not know their use. The purpose of the implementation of this activity is the preparation and technique of providing additional feed with fermentation technology that uses materials based on Indigofera and Sorghum, and the preparation and technique of making complete feed based on Indigofera and Sorghum. The method is the planting of Indigofera and Sorghum using automatic watering technology then making fermentation indigofera and sorghum as animal feed. Given land as a planting place Indigofera and Sorghum facilitated by partners and apply science and technology for the source of animal feed materials and fermentation of animal feed materials.